Italian immigration in southern Brazil: Reproduction and innovation in the layout of rural houses through the space syntax theory - Trusiani, Elio; Rigatti, Decio (Oculum Ensaios, 2016)
The structure of a sample of rural houses built by Italian immigrants in Southern Brazil from the last quarter of the 19th century onwards and a sample of Italian rural houses were analyzed using the space syntax theory and techniques. The samples were analyzed to identify key differences in the house genotypes. The main goal of the article is to compare the results regarding the Brazilian sample of houses with the Italian sample of rural houses from the regions of Veneto and Trentino Alto‑Adige, where most of the families that had moved to Southern Brazil came from. Therefore, it will be possible to evaluate whether or not, and to which extent, the Italian immigrants reproduced in Brazil the Italian house structures they used to live in and, more importantly, the relationship between the spatial structure of the houses built in Brazil and the patriarchal social structure that governed the entire society at that time. We inferred so far that the main genotype found in the Italian sample corresponds to the genotype produced in Brazil, a time when the houses were organized around the daily life of the families and suited the prevailing patriarchal social structure. In the Brazilian case, liminal events and a more flexible house plan are able to introduce differences in the way the same house can function, depending on how strangers are admitted into the houses on liminal occasions and in the daily life of the families. In Italy, this kind of flexibility is not found. There are two main hypotheses regarding this aspect: the first one is that the immigrants tend to reproduce the structure of the houses as experienced in Italy but, at the same time, they tend to introduce in Brazil a new typology of houses based on the flexibility of the house plan that is relatively autonomous from their spatial experience in Italy. KEYWORDS: Domestic space. Rural houses. Italian immigration in Brazil.